2019
DOI: 10.1177/1043659619841586
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management of Type 2 Diabetes in Adult Haitian Immigrants: A Qualitative Study

Abstract: Introduction: A large body of literature exists on self-management of type 2 diabetes (T2D) in a variety of populations. However, research is limited on how Haitian immigrants self-manage their T2D despite a prevalence of 6.9% in Haiti. The purpose of this study was to explore and describe the lived experience of adult Haitian immigrants managing T2D living in the United States. Methodology: Moustakas’s phenomenological approach guided this qualitative study. Adult Haitian immigrants diagnosed with T2D for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…8 The prevalence of T2DM in Haitian immigrants is difficult to quantify, in part because they are often categorized with other Black/non-Hispanics in government census reports. [8][9][10] Although studies have shown that this classification may contribute to treatment errors and health disparities among Haitian immigrants, [8][9][10] in government surveys and labor statistics reports, the category of Black/non-Hispanic includes all persons of color.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 The prevalence of T2DM in Haitian immigrants is difficult to quantify, in part because they are often categorized with other Black/non-Hispanics in government census reports. [8][9][10] Although studies have shown that this classification may contribute to treatment errors and health disparities among Haitian immigrants, [8][9][10] in government surveys and labor statistics reports, the category of Black/non-Hispanic includes all persons of color.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the perceptions and cultural beliefs regarding health and causes of disease among Haitian immigrants differ from those of other Black populations. 8,9,11,12 In the Haitian culture, a disease is viewed as a curse (eg, punishment from God or evil spells), and such a belief makes the management of chronic diseases challenging. 9,12,13 These notions regarding health and disease are related to their nation of origin and different experiences and sensibilities that shape their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations